THE INFLUENCE OF MACROECONOMIC CONDITIONS ON CREDIT RISK: CASE OF ROMANIAN BANKING SYSTEM - Bucur, Iulia Andreea; Dragomirescu, Simona Elena (Studies and Scientific Researches. Economics Edition, 2014)
This paper aims to explore the interactions between macroeconomic conditions, such as: real GDP growth rate, inflation rate, market interest rate, broad money supply, foreign exchange rate fluctuation and unemployment rate, and credit risk in Romanian banking sector during 2008-2013. The interrelations of indicators’ complexity imply a multidimensional statistical analysis in order to find a relation between the macroeconomic conditions and the credit risk. Our regression analysis findings confirm the hypothesis according to which the money supply growth rate and the market foreign exchange rate are negatively related with credit risk and the unemployment rate is positively related with it. Furthermore, our findings revealed that the credit risk is significantly and negatively affected by the exchange rate fluctuation and significantly and positively affected by the unemployment rate. The results do not indicate a significant relationship between credit risk and real GDP growth rate.